Stability for Functional Equation of Mixed Type in Non-Archimedean Normed Spaces - Ick-Soon Chang; Yang-Hi Lee (Journal of Function Spaces)
We take into account the stability of the following functional equation f(x+ay)+f(x-ay)-2f(x)-a2f(y)-a2f(-y)=0 in non-Archimedean normed spaces.